Digital competencies and skills as a determinant factor in Higher Education: A bibliometric analysis - Fernández Jiménez, Ana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper focuses on contributing to a better understanding of the study of Digital Competencies, Digital Skills in Higher Education. First, we have developed a descriptive analysis of journals and authors to understand the meaning of digital competencies and skills and their development in Higher Education. Secondly, we have analysed the conceptual knowledge using Web of Science; its use is growing rapidly in the research of articles or topics, being considered a topic to investigate and explore due to its importance and relevance.